(untitled) (AL MUNAZHZHARAH, 2019)
Forming a happy family and meeting with offspring is a core goal of marriage and is the hope of all married couples, but in fact not a few couples who decide to divorce after living together. This study aims to determine the post-divorce legal consequences in the perspective of Islamic Law Compilation. The method in this study uses a normative juridical qualitative research approach, with a basic research design or pure research. Sources of data in this study came from primary data and secondary data collected by library data collection methods. Furthermore, the data are analyzed through three stages namely: data reduction, data presentation, and data verification. The legal consequences of divorce are due to the mut’ah giving of a husband who divorces his wife, the period of iddah that must be lived by a divorced wife, both divorce and divorce, death rights for child care (hadhanah) for divorced husband and wife, and division of shared assets . Based on data analysis, it can be concluded that due to post-divorce law in the perspective of the Compilation of Islamic Law is having a legal effect on the obligation to give divorced husband to wife and divorced, the period of iddah for the wife is seen from a variety of circumstances and conditions, mothers are more entitled to child care ( hadhanah) that are not yet mumayyiz, and the shared property is shared equally, each getting one-half.